A contribution towards knowledge of the world literature regarding Braconidae (Hymenoptera: Braconidae). - Shenefelt, Roy D. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
A contribution toward knowledge of the world literature dealing with members of the Hymenopterous family Braconidae is presented for use by investigators of the family, individuals working in the field of biological control, persons dealing with the genetics of Habrobracon, and those interested in the general fields of parasitology, population dynamics and ecology of beneficial insects.